Low-intensity cigarette smoking and mortality risks: a pooled analysis of prospective cohort studies in Japan. (30th October 2021) - Inoue-Choi, Maki; Freedman, Neal D; Saito, Eiko; Tanaka, Shiori; Hirabayashi, Mayo; Sawada, Norie; Tsugane, Shoichiro; Usui, Yoshiaki; Ito, Hidemi; Wang, Chaochen; Tamakoshi, Akiko; Takeuchi, Taro; et al.
Abstract: Background: Increasing proportions of smokers in Japan smoke <10 cigarettes per day (CPD). Yet, the health risks of low-intensity smoking in Asia are poorly understood. Methods: We performed a pooled analysis of 410 294 adults from nine population-based prospective cohort studies participating in the Japan Cohort Consortium. Cigarette-use data were collected at each study baseline in 1983–1994. Study-specific hazard ratios (HRs) and 95% confidence intervals (CIs) for all-cause and cause-specific mortality were calculated using multivariable-adjusted Cox regression by CPD among current smokers and by age at cessation among former smokers, with never smokers as the referent group. Pooled HRs and CIs were computed using a random-effect model. Results: The smoking prevalence was 54.5% in men and 7.4% in women. About 15.5% of male and 50.4% of female current smokers smoked 1–10 CPD (low-intensity). Both male and female low-intensity smokers had higher all-cause mortality risks than never smokers. Risks were further higher with increasing CPD in a dose–response manner. HRs (95% CIs) were 1.27 (0.97–1.66), 1.45 (1.33–1.59) and 1.49 (1.38–1.62) for 1–2, 3–5 and 6–10 CPD, respectively, in men; 1.28 (1.01–1.62), 1.49 (1.34–1.66) and 1.68 (1.55–1.81) for 1–2, 3–5 and 6–10 CPD, respectively, in women. Similar associations were observed for smoking-related causes of death. Among former low-intensity smokers, younger age at cessation was associated with lower mortality risk. Conclusions: Smoking very low amounts was associated with increased mortality risks in Japan. All smokers should quit, even if they smoke very few CPD.